Eindexamen 2007. - Soons, Caroline; Akademie voor Kunst en Vormgeving, 's-Hertogenbosch; AKV St. Joost, Breda ('s Hertogenbosch : AKV/St. Joost, Avans Hogeschool, 2007)
Wijnen, Marieke ; Tiekstra, Femke ; Ruedisueli, Antoine ; van Mierlo, Emmely ; Meijer, Jos ; Chel, Michka ; Hendriksen, Marieke ; Hazenak, Emma ; Donders, Bram ; Debled, Cédric ; Bos, Jasper ; et al.
AKV St. Joost in Breda en 's-Hertogenbosch, 30 juni t.e.m. 4 juli 2007
kunstcatalogus